A study on how franchisees finance their owner's contribution when buying a franchise - Ngqola-Sebone, Lumka (Graduate School of Business (GSB), 2021)
The South African economy has been lagging its forecasted economic growth statistics in recent years, particularly following the worldwide economic recession of 2008. The year-on-year economic growth of South Africa is forecasted to continue to be lower than other developing countries. SMMEs are a significant contributor to a countries GDP and most franchises are classified as SMMEs. Entrepreneurs in the SMME space often use franchises to not only penetrate the market but to grow existing ventures. In its annual report for the year 2016, the Franchise Association of South Africa (FASA) states that the franchise industry contributed an estimated 11.6% to South Africa's GDP. When applying for finance at most institutions, prospective franchisees are required to also contribute to the total funding required; this is known as owner's contribution. This study explores what challenges franchisees experience in trying to raise owners' contribution and how the y overcame these challenges. It further explores what prospective franchisees can learn from the experiences of the participants. Through research conducted predominantly through an online survey and interviews to a limited extent, this study found that the franchise model has many advantages, but also has disadvantages. One of the main disadvantages remains the accessibility of finance, particularly that most financiers and franchisors require substantial owners' contribution. Many participants faced challenges when having to raise owner's contribution They most used personal savings and donations or borrowings from friends and family. The negative impacts that were identified were mainly personal stress and anxiety, strained personal relationships and delays in personal and/or business plans. In conclusion, in attempting to address these challenges highlighted by participants, recommendations are made to all stakeholders on how to overcome some of the challenges identified.